2011
DOI: 10.1590/s0103-21002011000600009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das medidas de oximetria de pulso em indivíduos sadios com esmalte de unha

Abstract: Objective: To evaluate the changes in measurements of pulse oximetry in healthy individuals with nail polish. Methods: Cross sectional study with 80 healthy volunteers. The colors of enamel used to assess oxygen saturation (SpO2) were: coffee with milk, coffee, chocolate, red and plum. These colors were distributed among the finger nails of his left hand. The fingers of the right hand were the controls. Results: The colors red (p = 0.047) and coffee (p = 0.024) showed lower values in SpO2 in comparison to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Decreases in pulse oximetry readings of 3% to 5% have been reported, depending on the absorption of red and infrared light when green, black, red, blue, or brown colored nail polishes are present [1,32,54]. However, some studies claim that the observed changes are not clinically significant [21,54].…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in pulse oximetry readings of 3% to 5% have been reported, depending on the absorption of red and infrared light when green, black, red, blue, or brown colored nail polishes are present [1,32,54]. However, some studies claim that the observed changes are not clinically significant [21,54].…”
Section: Introductionmentioning
confidence: 99%